Data from: Historical human activities reshape evolutionary trajectories across both native and introduced ranges ... - Einfeldt, Anthony (Dryad, 2019)
The same vectors that introduce species to new ranges could move them among native populations, but how human‐mediated dispersal impacts native ranges has been difficult to address because human‐mediated dispersal and natural dispersal can simultaneously shape patterns of gene flow. Here, we disentangle human‐mediated dispersal from natural dispersal by exploiting a system where the primary vector was once extensive but has since ceased. From 10th to 19th Centuries, ships in the North Atlantic exchanged sediments dredged from the intertidal for ballast, which ended when seawater ballast tanks were adopted. We investigate genetic patterns from RADseq‐derived SNPs in the amphipod Corophium volutator (n = 121; 4,870 SNPs) and the annelid Hediste diversicolor (n = 78; 3,820 SNPs), which were introduced from Europe to North America, have limited natural dispersal capabilities, are abundant in intertidal sediments, but not commonly found in modern water ballast tanks. We detect similar levels of genetic ... : Corophium_batch_1filtered Genetic data for Corophium volutator generated from ddRADseq Hediste_batch_1filtered Genetic data for Hediste diversicolor generated from ddRADseq ...